DRTA: A STRATEGY FOR INTEGRATING READING PURPOSE AND CRITICAL THINKING OF STUDENTS IN READING TEXT (RETAIN, 2014)
Abstract This journal highlights the findings of a study of the implementation of directed reading-thinking activity (DRTA) in teaching-learning process of reading descriptive text. The aim of the study was to describe how the DRTA strategy was implemented in a junior high school. The data were taken from observation. The result reveals that the DRTA was implemented by integrating students’ purpose and critical thinking while they were in reading activity. Kata Kunci: isi, format, artikel. Abstrak Jurnal ini menyoroti temuan-temuan dalam penelitian mengenai penerapan directed reading-thinking activity dalam proses belajar-mengajar membaca teks descriptive dalam lingkungan sekolah SMP. Tujuan diadakannya penelitian ini untuk memberi gambaran penerapan strategi DRTA. Data diambil dari hasil observasi. Hasil penelitian menunjukkan bahwa DRTA diterapkan dengan cara mengintegrasikan kemampuan siswa dalam membuat tujuan dalam membaca dan pemikiran kritis mereka terhadap teks yang diberikan. Keywords: content, formatting, article.